Increased Knowledge about First Treatment in Snake Bite Cases for Health Cadres - Hermawati, Hermawati; Mulyaningsih, Mulyaningsih; Widarti, Rini (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Data from the World Health Organization shows that snake bites in the world kill up to 4.5 million people every year. More than 15,000 cases of snake bites are reported and treated in the ER per year. Venomous snake bites are a public health hazard worldwide. The public is expected to have a positive attitude and have good knowledge of first aid.  There is a phenomenon of inadequate prehospital treatment. People tend to provide first aid using traditional methods such as sucking wounds, tying snakebite wounds with rope. The aim of the activity is to increase health cadres' knowledge regarding the initial treatment of snake bites, so the activity that will be carried out is to provide health education regarding the first treatment of snake bite cases, followed by a demonstration of the first treatment of snake bites. Measuring the level of knowledge by conducting pre and post tests using a questionnaire. The results of this activity show that there is an increase in knowledge among health cadres after health education is carried out.